2008
DOI: 10.1093/mutage/gen020
|View full text |Cite
|
Sign up to set email alerts
|

Supplementation of melatonin protects human lymphocytes in vitro from the genotoxic activity of melphalan

Abstract: Melatonin (MLT) is a natural oncostatic factor of the human body as well as an antioxidant thus protects the nuclear DNA from oxidative damage. It also has the ability to reduce the side effects of various drugs when used as a combination therapy. The anti-neoplastic agent melphalan (MEL), which encompasses a number of side effects, is a strong alkylating agent and a potent inducer of sister chromatid exchanges (SCEs). The aim of the current in vitro study was to investigate the ability of MLT to reduce the ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 70 publications
1
19
0
1
Order By: Relevance
“…Evaluation of MIs and PRIs was based on the 2 test. Bivariance correlations between SCEs and MIs or SCEs and PRIs were also calculated [22,23,28,33] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evaluation of MIs and PRIs was based on the 2 test. Bivariance correlations between SCEs and MIs or SCEs and PRIs were also calculated [22,23,28,33] .…”
Section: Discussionmentioning
confidence: 99%
“…SCEs are considered as a more sensitive method than chromosome aberrations since induced DNA damage can be demonstrated by the formation of SCEs even at low concentrations of genotoxic agent [20][21][22][23] .…”
mentioning
confidence: 99%
“…The cultures were accordingly harvested following the completion of the incubation period. Chromosome preparations were performed using a slightly modified method of fluorescence plus Giemsa (FPG) (Goto et al 1978;Lialiaris et al 2008).…”
Section: Cytogenetic Testingmentioning
confidence: 99%
“…Various in vitro and in vivo studies have shown that melatonin protects against genotoxicity, cardiotoxicity, nephrotoxicity and neurotoxicity results from chemotherapeutic agents [31][32][33][34]. But melatonin is not effective for the protection of chemotherapy-induced DNA damage because of its short half-life.…”
Section: Introductionmentioning
confidence: 99%